2020
DOI: 10.13189/ujer.2020.081004
|View full text |Cite
|
Sign up to set email alerts
|

M-Learning Boost Students' Motivation in Learning Arabic Language Proficiency for Elementary Level

Abstract: The language acquisition is one of the most important criteria that contribute to the measurement of language proficiency for students and the objectives of teaching of Arabic in Malaysia are currently based on the Standard Arabic Curriculum, which focuses on mastery of the four language skills. However, the inability to master the four language skills is still very significant. This occurs due to the fact that students only learn Arabic to pass the exam and that learning strategies applied to the students are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Furthermore, this study is consistent with Gonen and Akbarov (2016), which demonstrated that students utilised satisfaction as their preferred LLS. Wan Daud et al (2020) reported the same findings in their study, which indicated that students learning Arabic through mobile apps had the highest mean score in satisfaction components of motivating factors.…”
Section: Conclusion 51 Summary Of Findings and Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Furthermore, this study is consistent with Gonen and Akbarov (2016), which demonstrated that students utilised satisfaction as their preferred LLS. Wan Daud et al (2020) reported the same findings in their study, which indicated that students learning Arabic through mobile apps had the highest mean score in satisfaction components of motivating factors.…”
Section: Conclusion 51 Summary Of Findings and Discussionsupporting
confidence: 63%
“…The satisfaction subscale averaged the highest. A comparable study by Wan Daud et al (2020) revealed the highest satisfaction means. The study evaluated how mobile learning affects Arabic language learning motivation.…”
Section: Past Studies On the Use Of Learning Strategies And Arcs Moti...mentioning
confidence: 72%
See 2 more Smart Citations
“…Han and Yin explained that students have high motivation in learning as evidenced by their attention to the explanations of the teachers (Han & Yin, 2016). Daud et al also stated that every student who has high motivation can be seen from the attention to the lesson (Daud et al, 2020).…”
Section: Asking To Gain Understandingmentioning
confidence: 99%